66 Should we offer multi-gene testing to all patients with breast cancer: a cost-effectiveness analysis. (18th September 2019) - Sun, L; Brentnall, A; Patel, S; Buist SM, D; Bowles JA, E; Evans R, DG; Eccles, D; Hopper, J; Li, S; Duffy, S; Cuzick, J; dos-Santos-Silva, I; et al.
Abstract : Objectives: To estimate incremental lifetime-effects, costs, cost-effectiveness and population impact of multigene-testing all BC patients compared to current practice of family-history/clinical-criteria based genetic ( BRCA )-testing. Methods: Cost-effectiveness microsimulation modelling study comparing lifetime costs-&-effects of BRCA1/BRCA2/PALB2 (multigene) testing all unselected BC-cases (Strategy-A) with family-history/clinical-criteria based BRCA1/BRCA2 -testing (Strategy-B) in both UK and US populations.Data obtained from 11, 836 population-based BC-patients (regardless of family-history) recruited to four large research studies in the UK (Predicting-Risk-of-Breast-Cancer-at-Screening (PROCAS: 1389 out of 57, 000 women) & Prospective-Outcomes-in-Sporadic-versus-Hereditary-breast-cancer (POSH: 2885) studies); US (Kaiser-Permanente Washington Breast-Cancer-Surveillance-Consortium (BCSC) registry: 5892 out of 132, 139 women) and Australia (Population-based BC-cases of the Australian-Breast-Cancer-Family-Study (ABCFS: 1670 women)). The main outcome measure was the incremental cost per quality-adjusted life-year (QALY) gained with a 3.5% annual discount. Parameter uncertainty was explored using one-way and probabilistic sensitivity analyses. Results: Compared with current clinical-criteria/family-history-based BRCA -testing, ( BRCA1/BRCA2/PALB2 ) multigene-testing for all BC-patients would cost £10, 470/QALY (UK) or $58, 702/QALY (US) gained, well below UK/NICE and US cost-effectiveness thresholds of £30, 000/QALY & $100, 000/QALY. Probabilistic sensitivity-analysis shows unselected multigene-testing remains cost-effective for 98% UK/77% US health-system simulations. One year's unselected panel-genetic testing can prevent 1, 776 BC/OC-cases and 557 deaths in the UK; and 8, 258 BC/OC-cases and 2, 143 deaths in the US. Correspondingly, 7 UK/32 US excess heart-disease deaths occur annually. Conclusions: Unselected multigene-testing for all BC patients is extremely cost-effective compared with family-history/clinical-criteria testing for UK and US health-systems. It prevents thousands more BC/OC cases and deaths. We recommend changing current policy to expand genetic-testing to all BC patients.